Treatment of neuroendocrine tumors: new recommendations based on the CLARINET study - Kos-Kudła, Beata (Contemporary Oncology/Współczesna Onkologia, 2015)
Somatostatin analogs (SSAs), including lanreotide, play a fundamental role in treatment of neuroendocrine tumors (NETs) of the gastrointestinal tract. SSAs control the clinical symptoms and are the treatment of choice in functioning NETs. Data indicating that SSAs have anti-proliferative activity has mainly come from prospective or retrospective observational studies. A recently published CLARINET study confirmed the anti-proliferative effect of lanreotide in a much broader range of NET patients than previously reported. As a result, it is now possible for clinicians to use lanreotide to treat patients with well-differentiated metastatic grade 1 and grade 2 GEP NETs (i.e., with a Ki-67 proliferative index < 10%) located in the pancreas, small intestine, or of unknown primary location, regardless of the degree of liver involvement. The results of the CLARINET study also challenge the current “wait and watch” strategy for NET treatment. Instead, it is proposed that SSAs are considered at an early stage of NET management, as already suggested by many organizations and scientific societies.